Emotion Network Analysis During COVID-19 Quarantine ‐ A Longitudinal Study - Martín-Brufau, Ramón; Suso-Ribera, Carlos; Corbalán, Javier (Frontiers in Psychology, 2020)
Introduction. The COVID-19 emergency has imposed important challenges in the lives of individuals, particularly since the restriction of free movement. In Spain, this mandatory home confinement started on March 14th 2020. In this scenario, some calls have been made to better understand the exact impact of quarantine on the emotional status of individuals across time. Material and Methods. The first day the Spanish government imposed quarantine, our team launched an online longitudinal study to monitor the emotional responses to the COVID-19 emergency over time. For two weeks, 187 people have responded to a daily diary on emotion functioning. An emotion network analysis was performed to study the network structure of 30 mood states and its changes during the two first weeks of the quarantine. Results. The emotional network showed critical changes in the interactions of emotions over time. An analysis of mean emotional levels did not show statistically significant changes in mood over time. Interestingly, two different network patterns were found when the sample was divided between those with favorable and unfavorable response. Discussion. This new approach to the study of longitudinal changes of the mood state network of the population reveals different adaptation strategies reflected on the sample’s emotional network. This network approach can help identify most fragile individuals (more vulnerable to external stressors) before they develop clear and identifiable psychopathology and also help identify anti-fragile individuals (those who improve their functioning in the face of external stressors). This is one of the first studies to apply an emotional network approach to study the psychological effects of pandemics and might offer some clues to psychologists and health administrations to help people cope with and adjust to this critical situation.